2015
DOI: 10.1136/annrheumdis-2014-207212
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of subclinical sonographic joint activity in rheumatoid arthritis in sustained clinical remission

Abstract: We conclude that subclinical joint activity is long-lasting in RA joints in clinical remission, but attenuates over time. The latter conclusion is based on the observed shorter time duration from last clinical activity for strong compared with weaker sonographic signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It has been observed that subclinical synovitis is long-lasting in RA patients in clinical remission [59]. In a study dated from 2012, pD, but not low-field MRI, predicted relapse and radiographic progression in RA patients with low levels of disease activity [60].…”
Section: Correlation Of Msus With Physical Examination Inflammatory mentioning
confidence: 99%
“…It has been observed that subclinical synovitis is long-lasting in RA patients in clinical remission [59]. In a study dated from 2012, pD, but not low-field MRI, predicted relapse and radiographic progression in RA patients with low levels of disease activity [60].…”
Section: Correlation Of Msus With Physical Examination Inflammatory mentioning
confidence: 99%
“…However, evidence exists that some patients with RA experience radiographic progression despite being in clinical remission [3]. This may be explained by the persistence of subclinical joint inflammation which can only be detected through sensitive imaging techniques such as MSUS and magnetic resonance imaging [4][5][6]. MSUS has been proved to be more sensitive than physical examination for the detection of synovitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the persistence of subclinical inflammation, found only by imaging modalities (Magnetic Resonance Imaging (MRI), MSUS). 16 There is evidence that the presence of a PD signal is a strong predictor of subsequent radiographic progression and a recent relapse in RA patients in remission. 17,18 In 2016, the International Task Group of experts in MSUS published a paper with 6 practical algorithms for the use of ultrasound in patients with RA in daily rheumatology practice.…”
Section: Msus As a Predictor Of Progression From Undifferentiated Artmentioning
confidence: 99%